Integration of Internet of Things Technology in Digital-Based Residential Security Application - Rajib Ghaniy; Binanda Wicaksana; Fahmi Arnes; Laras Melati; Helena Septiana (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
This study evaluates the usability of an IoT-based residential security application designed to improve guest registration and access control in housing environments. The system integrates multiple user roles, including administrators, residents, guests, and security officers, and utilizes QR Code verification to streamline entry procedures. Usability testing was conducted using the System Usability Scale (SUS) with 30 respondents. The results show an average SUS score of 74.83, indicating that the application falls within the “Good” usability category. Most users reported that the interface is intuitive, the functions are well integrated, and system navigation is easy to understand. Although minor improvements are still required—such as notification speed and icon clarity—the system is considered acceptable for public use. These findings demonstrate that IoT integration can enhance residential security operations while maintaining positive user experience.